Endoplasmic reticulum Ca2+ content decrease by PKA-dependent hyperphosphorylation of type 1 IP3 receptor contributes to prostate cancer cell resistance to androgen deprivation. Issue 4 (April 2015) - Boutin, Benoît; Tajeddine, Nicolas; Monaco, Giovanni; Molgo, Jordi; Vertommen, Didier; Rider, Mark; Parys, Jan B.; Bultynck, Geert; Gailly, Philippe
Graphical abstract